KEKUATAN HUKUM TANDA TANGAN DIGITAL DALAM PEMBUKTIANSENGKETA PERDATA MENURUT UNDANG-UNDANG NOMOR 11 TAHUN2008 TENTANG INFORMASI DANTRANSAKSI ELEKTRONIK - Ni Made Trisna Dewi; Ni Made Rai Sukardi (Jurnal Ilmiah Raad Kertha, 2023)
Digital signatures can provide a greater guarantee of document security than regular signatures. The recipient of the electronic message which is affixed with a digital signature can check whether the message really came from the correct sender and whether the message has been altered after being signed either intentionally or unintentionally in the case of electronic payment systems. The formulation of this research problem is how the authenticity of digital signatures according to Law Number 11 of 2008 concerning Electronic Information and Transactions and how the legal power of digital signatures in proving civil disputes is reviewed from Law Number 11 of 2008 concerning Electronic Information and Transactions. The research method used in this research is a type of normative research. The results of the discussion in this study are as follows: It needs to be well understood by legal practitioners that an electronic signature, not a scanned signature image is then placed on a document, so that a document is impressed (on a computer monitor screen) signed. The actual definition of an electronic signature (according to the ITE Law) can be made in various ways, including by means of a digital code that is attached to an electronically transmitted message, which will specifically provide a special identification of the sender. The strength of the burden of proof inherent in digital signatures in terms of proving that civil procedural law has the strength of the evidence burden at the level of an underhanded deed (ABT), therefore the strength of the evidence load inherent in signatures in electronic mail is only the strength of formal proof and material proof.